2010
DOI: 10.1007/s11274-010-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodesulfurization by magnetic immobilized Rhodococcus erythropolis LSSE8-1-vgb assembled with nano-γ-Al2O3

Abstract: Biodesulfurization activity can be enhanced by assembling nano-c-Al 2 O 3 particles on the magnetic immobilized Rhodococcus erythropolis LSSE8-1-vgb. The cells can be collected and reused conveniently by an external magnetic field. Firstly, cells were magnetic immobilized by coating with Fe 3 O 4 nano-particles. The optimal ratio of cells to magnetic Fe 3 O 4 nano-particles was determined to be 50:1 (g/g). Then nano-c-Al 2 O 3 adsorbents were assembled onto the cells to enhance the desulfurization activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…The sulfur atom is oxidized into sulfite and sulfate, which will be released to the aqueous phase (Kilbane 2006). Many studies have used DBT-degrading microorganisms to investigate the BDS capability of crude oil, gasoline and biodiesel (Oldfield et al 1997;Zhang et al 2011;Wang et al 2011). It was reported that 26-71 % of sulfur could be removed biologically from different petroleum oils, with the highest removal efficiency of sulfur from light crude oil (Bhatia and Sharma 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfur atom is oxidized into sulfite and sulfate, which will be released to the aqueous phase (Kilbane 2006). Many studies have used DBT-degrading microorganisms to investigate the BDS capability of crude oil, gasoline and biodiesel (Oldfield et al 1997;Zhang et al 2011;Wang et al 2011). It was reported that 26-71 % of sulfur could be removed biologically from different petroleum oils, with the highest removal efficiency of sulfur from light crude oil (Bhatia and Sharma 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fe 3 O 4 NPs coated mesoporous alumino-silicate minerals were used for ultra-deep desulfurization forhydro treated diesel [25], and nano-c-Al 2 O 3 coated by Fe 3 O 4 NPs enhanced biodesulfurization by Rhodococcus erythropolis assembly [26]. In this report, as shown in Fig.…”
Section: Morphological Study Of Magnetic Nanoparticlesmentioning
confidence: 79%
“…In order to recycle and reuse the biocatalysts, immobilized whole-cell biocatalysts are preferred as in this form they could be recycled for reuse, thereby avoiding the need to purify intracellular enzymes and reducing process costs [22,[29][30][31]. Entrapment seemed to be a [29,32].…”
Section: Biotransformation With Immobilized Biocatalystsmentioning
confidence: 99%